THE NEWLY DISCOVERED CLASSICAL PERIOD TOMBS OF GARNI - Gabrielan, Armine Araratovna (History, Archeology and Ethnography of the Caucasus, 2026)
This article is dedicated to the study of several burials from the Classical period that were accidentally uncovered during the installation of a water pipeline in the village of Garni, Kotayk Province, Republic of Armenia. In spring of 2022, a rescue excavation was carried out by a team from the Institute of Archaeology and Ethnography of the National Academy of Sciences of Armenia, during which one slab-lined cist burial and three jar burials were unearthed and documented. The first of the jar burials revealed a distinctive ritual burial practice: the remains of a mother and child were interred alongside the heads of a cow and a calf within the same grave. The other two jar burials were associated with children. The slab-lined cist burial, which yielded relatively richer grave goods, contained the remains of a 15–16-year-old adolescent girl. The burial assemblage included two locally produced ceramic vessels and one imported unguentarium, along with personal items, jewelry, and a metal pair of scissors. A palynological analysis of the soil residues from the vessels suggested that two of them had contained a substance likely used for treating skin diseases. Based on the recovered material, a 3D reconstruction of the cist tomb was created. Both through parallels with contemporaneous archaeological sites and on the basis of radiocarbon (¹⁴C) dating, the newly discovered burials of Garni are dated to the 3rd–2nd centuries BC through the 1st century AD. Their study significantly enriches our understanding of urban life in Armenia during the classical period, offering new insights into daily life, diet, clothing, adornment, medical practices, belief systems, and funerary rituals of the time.